Profesionalisme kaunselor sekolah rendah - Johari Talib (Universiti Kebangsaan Malaysia, 2009)
This paper presents a qualitative research report on primary school counselors’ professionalism. This study was based on detailed interviews between the researcher and 15 qualified primary school counselors graduated from one teachers’ institute. The outcomes of this research are divided into three parts following the research questions: pupils’ problems, counselors’ perceptions on their role as school counselor and counselors’ evaluation on courses and training they attended at the teachers’ institute. There are two categories of problems brought by primary school pupils to the counselors: Category 1 involved ordinary cases that can be easily solved by the counselors, Category 2 involved more serious cases which the counselors found difficult to handle due to four main obstacles. The four main obstacles are related to counselors’ self-efficacy, administrator’s red-tape, school and community’s attittudes towards counseling services and the effectiveness of counseling training courses attended. These problems need to be given attention to improve primary school counseling services